2022
DOI: 10.1111/jfpp.16335
|View full text |Cite
|
Sign up to set email alerts
|

Shelf‐life estimation of packaged dried foods as affected by choice of moisture sorption isotherm models

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…( 12)) of the permeation equation, and the values of the slope of the isotherm (b ) were employed to calculate the water-vapor permeance. The linear model parameters were similar to those reported for onion flakes, green beans, rice cakes, and dry tea (Lee and Robertson, 2022;Robertson and Lee, 2021). Table 3 presents the water-vapor permeances (P/X) values under different storage conditions, calculated using the linear and GAB model of the isotherm.…”
Section: Water-vapor Permeancesupporting
confidence: 67%
See 1 more Smart Citation
“…( 12)) of the permeation equation, and the values of the slope of the isotherm (b ) were employed to calculate the water-vapor permeance. The linear model parameters were similar to those reported for onion flakes, green beans, rice cakes, and dry tea (Lee and Robertson, 2022;Robertson and Lee, 2021). Table 3 presents the water-vapor permeances (P/X) values under different storage conditions, calculated using the linear and GAB model of the isotherm.…”
Section: Water-vapor Permeancesupporting
confidence: 67%
“…It is known that shelf-life simulations based on Fick and Henry's law depend on water vapor adsorption models. Lee and Robertson (2022) compared different adsorption models with respect to the packaged product's shelf-life and demonstrated that the linear and GAB models are the most suitable for predicting the shelf-life of a low-moisture packaged product. The GAB model is one of the most useful to describe the moisture adsorption isotherm up to water activities of 0.9 and provides information on the monolayer moisture content and the energetic interaction of the water with the surface of the food (Guadarrama-Lezama, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between moisture content and water activity in flours provides useful information about product hygroscopicity and stability. It is also a useful tool for establishing packaging materials and storage conditions [31]. As expected, the isotherms of the yellow cassava flours displayed an increase in equilibrium moisture content (EMC) with increasing water activity (Figure 5).…”
Section: Moisture Sorptionsupporting
confidence: 58%